Transformasi UMKM Menuju Ekonomi Digital melalui Pelatihan QRIS dan Pembuatan Spanduk Kreatif sebagai Sarana Promosi Usaha Desa Batu Karang, Kab. Karo - Aisyah Amelia Purba; Syanda Rabiatul Adwiya; Yuni Andriani Ritonga; Rania Atikah Putri; Yenti Arsini (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This research aims to describe the process of transforming Micro, Small, and Medium Enterprises (MSMEs) toward a digital economy through QRIS (Quick Response Code Indonesian Standard) training and the creation of creative banners as promotional media in Batu Karang Village, Karo Regency. Digital transformation has become an essential need for MSMEs to adapt to changes in consumer behavior and rapid technological development. This study employs a descriptive qualitative approach focusing on training materials and the implementation process, without using quantitative data or interview results. The findings indicate that QRIS training provides MSME actors with conceptual and practical understanding of digital payment systems that are efficient, secure, and convenient. In addition, creative banner development functions as a visual promotional tool that strengthens business identity and enhances consumer attraction. The integration of QRIS with creative banners creates synergy between digital payment systems and promotional strategies that are relevant to the conditions of rural MSMEs. Overall, this research demonstrates that digital-based training combined with creative promotional media can serve as an effective strategy to enhance MSME readiness in facing the digital economy era in a sustainable manner.